The efficiency model of soccer player's actions in cooperation with other team players at the FIFA World Cup - Szwarc, A. (Human Movement, 2008)
The purpose of this paper is to present a simple, table-graphic model of one-to-one play in soccer based on observation of cooperation of top soccer players. Basic procedures. The research material consisted of audio-visual recordings from six soccer matches played by the three top teams of the 2006 World Cup finals. The data concering one-to-one plays was entered on a special form. Offensive and defensive actions were assessed with reference to the implementation of the game's objectives and players' position in the field zones. Main findings. It has been proven that elite soccer players are most effective at intercepting the ball down the field and in other zones of the pitch. They are also very active in breaking their opponents' offensive actions in midfield. Conclusions. The models reflecting elite soccer players' efficiency in one-to-one play should constitute important references for the training of novice soccer players.